ANALYSIS OF THE POTENTIAL OF NATURAL RESOURCES SPORTS TOURISM IN SANGGAU DISTRICT - Tandiyo Rahayu; Agung Wahyudi; Suin (Universitas Negeri Semarang, 2024)
Sports tourism has the same goal as other tourism, namely achieving pleasure and excitement to relieve boredom due to work. In this study, 2 research questions are asked, namely: what is the potential for natural resource-based tourism in Sanggau Regency, Sekayam District and how is the mapping and management of sports tourism potential in Sanggau Regency, Sekayam District. The research approach uses a qualitative descriptive method. This approach is an approach used to analyze research subjects thoroughly using natural descriptions of objects. The focus of this research is on the process of investigation and understanding based on research on problems in the analysis of sports tourism potential based on natural data sources in Sanggau Regency. The results of the research conclude that the potential for natural resource-based tourism in Sanggau Regency, Sekayam District is famous for its natural tourist attractions. However, due to poor management, the target for each event held will of course be different every year due to less than optimal implementation. The concept of organizing natural resource-based tourism activities can be in the form of a sport tourism event by combining the two sports and tourism activities together which are believed to have a positive impact on regional progress. The mapping and management of sports tourism potential in Sanggau Regency, Sekayam District at the Padong Prince Pati tourist attraction has basically carried out sports tourism-based activities in the form of Selumak Perahu Bidar which is an annual event as one of the activities to promote tourist areas so that tourist visits will increase after the activity takes place. However, the implementation and management of these activities was not optimal, so the researchers concluded that the sport tourism event managed by Padong Pangeran Pati was in the adequate category.